Ethical, legal, and managerial challenges in digital health governance in Brazil’s Unified Health System (SUS) - Mario Angelo Cenedesi Junior; Oldair Donizete Galeni; Siglia Sousa de França; Priscila Rocha Santos; Thaita Thaisi Zago; Dulcyane Ferreira de Oliveira; Mônica Rodrigues da Silva; Samuel Ribeiro Martins; Junamappe da Silva Cardoso Mendes; Maria Cristina de Moura-Ferreira (Aposta: Revista de Ciencias Sociales, 2026)
Digital transformation is increasingly reshaping health systems, altering how healthcare is delivered, information is generated and exchanged, decisions are made, and public services are governed. In Brazil, this transformation occurs within the Unified Health System (Sistema Único de Saúde – SUS), a universal and decentralized health system whose governance depends on coordination among federal, state, and municipal authorities, health professionals, civil society, and an increasingly complex ecosystem of technological actors. Although Brazil has developed a substantial digital health infrastructure and established national policies for digital transformation, the expansion of digital health raises challenges that extend beyond technological implementation. This article examines the ethical, legal, and managerial challenges involved in governing digital health in the SUS. It argues that digital transformation should not be understood merely as the incorporation of information and communication technologies into healthcare, but as a transformation of the institutional arrangements through which health information, decisions, responsibilities, and public resources are governed. Particular attention is given to privacy and data protection, equity and digital inclusion, transparency, accountability, interoperability, cybersecurity, institutional capacity, professional competencies, technological dependence, and the regulation of emerging technologies. The analysis highlights tensions between innovation and regulation, data use and privacy, efficiency and equity, decentralization and coordination, and public interest and private technological interests. By integrating ethical, legal, and managerial perspectives, the article proposes a governance-oriented understanding of digital health transformation in the SUS and discusses the institutional conditions required to ensure that digitalization strengthens rather than undermines the principles of universality, equity, comprehensiveness, democratic participation, and public accountability that underpin the Brazilian health system.